Berufs- und wirtschaftspädagogische Analysen Aktuelle Forschungen zur beruflichen Bildung - Faßhauer, Uwe; Fürstenau, Bärbel; Wuttke, Eveline (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2012)
The authors deal with empirical and theoretical questions of current vocational and business education research. In addition to disciplinary reflections and analyses on teaching/learning research in vocational education and training, the authors also deal with the professionalisation of personnel in vocational education and training as well as current research findings on the subject of vocational qualification and further training.